Exposure to chlorantraniliprole affects the energy metabolism of the caddisfly Sericostoma vittatum - Rodrigues, Andreia C M; Gravato, Carlos; Quintaneiro, Carla; Bordalo, Maria D; Golovko, Oksana; Žlábek, Vladimír; Barata, Carlos; Soares, Amadeu M V M; Pestana, João L T (Environmental toxicology and chemistry, 2017)
Caddisflies have been included in ecotoxicological studies because of their sensitivity and ecological relevance. The present study aimed to assess the sublethal effects of an anthranilic diamide insecticide, chlorantraniliprole (CAP), to Sericostoma vittatum. Used worldwide, CAP is a persistent compound that has been found in surface waters at concentrations from 0.1 μg/L to 9.7 μg/L. It targets the ryanodine receptors, and the present ecotoxicological assessment focused on biomarkers related to neurotransmission, biotransformation, oxidative stress damage, and endpoints related to energy processing (feeding, energy reserves, and cellular metabolism). Six days of exposure trials revealed that feeding activity was significantly decreased in S. vittatum larvae exposed to 0.9 μg/L CAP. Concomitantly, a reduction in cellular metabolism and a significant decrease in protein content were also observed in caddisfly larvae exposed to CAP, suggesting metabolic depression. The results show that sublethal concentrations of CAP can cause detrimental sublethal effects on S. vittatum total glutathione content at concentrations as low as 0.2 μg/L. Bioenergetics can be used to assess physiological effects of contaminants, and the present results show that exposure to low, environmentally relevant, concentrations of CAP alter energy acquisition and metabolism in nontarget aquatic insects with potential population level effects. Environ Toxicol Chem 2017;36:1584-1591. © 2016 SETAC.
Keywords: ortho-Aminobenzoates; Animals; Oxidative Stress; energetický metabolismus; Larva; zvířata; hmyz; biologické markery; oxidační stres; Energy Metabolism; Insecticides; Biomarkers; Insecta; insekticidy; larva; ortoaminobenzoáty